Edukacja i informatyzacja społeczeństwa jako czynniki kształtujące gospodarkę opartą na wiedzy - implikacje dla Polski - Klonowska-Matynia, Maria; Granosik, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
This article undertakes to discuss the issue of realization of building strategy of the knowledge-based economy in Poland, with much consideration given to two particular factors: education system and development of information society. The article does not exhaust the issue of human capital and knowledge in creating the knowledge-based economy (GOW); it merely highlights important aspects of possibility of developing it in Poland. For the purposes of this article, the majority of data have been acquired from the Central Statistical Office as well as the reports from the recent years of higher education and the Patent Office of Republic of Poland. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1191, s. 213-225